Identifikasi Risiko Kecelakaan dan Keselamatan Kerja (K3) pada Pelaksanaan Proyek Konstruksi di Sumatera Selatan - Amalia, Kiki Rizky; Situmeang, Sheragizca Yolanda; Syapawi, Ahmad; Dzaky, Akhmad; Zhafirah, Na’ilah; Agustian, Ragil (Universitas Batanghari Jambi, 2025)
The construction industry is one of the sectors with a high level of risk, particularly concerning Occupational Health and Safety (OHS). These risks may include potential workplace accidents, schedule delays, cost overruns, asset damage, and disruptions to work quality. Understanding and managing these risks is crucial to minimizing the negative impacts that may arise during project execution, including in South Sumatra Province. This study aims to identify risks that emerge due to the lack of OHS implementation in construction projects, in order to formulate strategies for risk prevention and mitigation. Data collection was carried out by distributing questionnaires to respondents from 5 building construction projects and 8 civil construction projects in South Sumatra, involving a total of 31 respondents.The analysis reveals that the highest risks in building construction projects include falling from heights, injuries caused by manual tools, and being struck by heavy equipment. Based on the data, the risk identification indicates that falling from heights is the most frequent incident. These three risks consistently received a mean score of 5, indicating a very high category in risk assessment. The causes of these risks include the failure to use Personal Protective Equipment (PPE) and unsafe, hazardous, or unhealthy workplace conditions. Risk control measures that are routinely implemented include the installation of OHS signage and safety lines, regular OHS communication with workers, routine inspections and evaluations of tools and heavy equipment, and the availability of work methods and programs. To further reduce these risks, risk control is carried out following the hierarchy of controls, beginning with Personal Protective Equipment (PPE), Administrative Controls, Engineering Controls, Substitution, and Elimination.